Psychotherapy cognitive conductual in the obesity treatment - Larrañaga, Alejandra (2007)
Obesity is a chronic disease. The treatment of adult obesity is difficult and long-term results often are disappointing. Current management of this disease is bases in the modification of the lifestyle, mainly regarding to eating habits and physical activity. Modification of any habit requires the use of specific psychological methods. In the present article we propose the use of cognitive- behavioral therapy as adjuvant in the regular therapy of obese patients, in order to maintain the loss weight